2004
DOI: 10.1038/modpathol.3800053
|View full text |Cite
|
Sign up to set email alerts
|

High-grade prostatic intraepithelial neoplasia

Abstract: High-grade prostatic intraepithelial neoplasia (PIN) is now accepted as the most likely preinvasive stage of adenocarcinoma, almost two decades after its first formal description. PIN has a high predictive value as a marker for adenocarcinoma, and its identification warrants repeat biopsy for concurrent or subsequent invasive carcinoma. The only method of detection is biopsy; PIN does not significantly elevate serum prostate-specific antigen (PSA) concentration or its derivatives and cannot be detected by curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
1
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(139 citation statements)
references
References 177 publications
6
122
1
10
Order By: Relevance
“…This indicates that the prostate cancer risk is increased with the increase in the number of specimens found to have HGPIN on the 1 st biopsy. Our result also agreed with that of Bostwick et al [2], Abdel-khalek et al [23] and Rosser et al [27], However, it disagreed with studies that revealed lower prostate detection rate (De Nunzio et al [22], Kamoi et al [28] and Epstein & Herawi [29]) and other studies with higher prostate detection rate (Keetch et al [30] and Borboroglu et al [25]). …”
Section: Discussionsupporting
confidence: 37%
“…This indicates that the prostate cancer risk is increased with the increase in the number of specimens found to have HGPIN on the 1 st biopsy. Our result also agreed with that of Bostwick et al [2], Abdel-khalek et al [23] and Rosser et al [27], However, it disagreed with studies that revealed lower prostate detection rate (De Nunzio et al [22], Kamoi et al [28] and Epstein & Herawi [29]) and other studies with higher prostate detection rate (Keetch et al [30] and Borboroglu et al [25]). …”
Section: Discussionsupporting
confidence: 37%
“…The American Cancer Society National Prostate Cancer Detection Project identified prostatic intraepithelial neoplasia (PIN) and cancer in 17 (5.2%) and 58 (15.8%) men, respectively, from a series of 330 biopsies from men participating in an early detection project. 1 Other studies have found high-grade PIN in up to 16.5% of contemporary needle biopsy specimens in urology office practice. [2][3][4] The diagnosis of HGPIN is predictive of subsequent cancer detection in 2.3-100% of patients.…”
mentioning
confidence: 99%
“…For the genetic and molecular evidence, HGPIN and prostate cancer have both raised rates of cell proliferation and cell death [18,19] and raised rate of neovascularization [1] compared with those in normal prostate. They are also phenotypically and morphometrically similar [1] and they share common molecular and genetic alterations [20], although the basal cell layer is disrupted in HGPIN and absent in prostate cancer [21]. …”
Section: Discussionmentioning
confidence: 99%